Efektivitas Penerapan Model Pembelajaran Problem-Based Learning dalam Pendidikan Agama Islam Siswa SMAN 10 Batanghari - Fitrisia, Rosi; Nurmadiah, Nurmadiah (ISLAMIKA, 2024)
This study evaluates the effectiveness of implementing the Problem-Based Learning (PBL) method in Islamic Religious Education (PAI) teaching for 10th-grade students at SMAN 10 Batanghari. The primary goal of this research is to enhance students' understanding, engagement, and collaboration skills through a more interactive and contextual approach. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using thematic analysis techniques. The results indicate that the application of the PBL method positively impacts students' understanding of PAI material, particularly on the topic "Avoiding Free Association to Protect Human Dignity and Honor." Furthermore, this method also increases student engagement and motivation, as well as strengthens their collaboration and communication skills. However, the study also identifies several challenges, including students' difficulties in time management and independent information-seeking, as well as limited access to technology and resources. These findings suggest that to maximize the effectiveness of PBL, additional teacher training and adequate resource provision are required. This research makes a significant contribution to the development of more effective and relevant PAI teaching strategies that meet current students' needs.